Elevated levels of exhaled nitric oxide in patients with anorexia nervosa - Oświęcimska, Joanna (Springer Berlin Heidelberg, 2013)
BACKGROUND: Nitric oxide (NO) is involved in eating behavior and inflammatory response. Moreover, there is evidence that NO production is altered in patients with anorexia nervosa (AN). AIM: To assess whether the overproduction of NO in AN can affect NO level in exhaled air. MATERIALS AND METHODS: Exhaled NO level was studied in 23 girls with AN and compared with that of healthy age- and gender-matched nonatopic controls. RESULTS: Exhaled NO levels were significantly higher in girls with AN compared with healthy age-matched controls. CONCLUSIONS: It appears that anorexia nervosa was accompanied by a higher level of exhaled NO, likely resulting from a systemic increase in NO production because of the severe catabolic state.